Airport expansion: The Malaysian experience of KLIA2 - Sahrir, Syazwani; Khalid, Ummi Aqilah; Bohari, Zulfadly Azizi; Bachok, Syahriah; Mohamed Osman, Mariana (2012)
The paper describes the Malaysian experiences with airport expansion. Increase in international and domestic air travel has resulted in increased demand for airport facilities. In Malaysia, the rise of low-cost air travel has had the government revising the current capacity of the international airport provision. This research relates the experiences of major expansion phases of the second Kuala Lumpur International Airport, which is also known as KLIA2. It dwells into the anticipated environmental impacts of such expansion.